Ancient Roman Coins from the Republican Age to the Imperial Age: A Multi-Analytical Approach - Caterina De Vito; Martina Bernabale; Carlo Aurisicchio; Fiorenzo Catalli; Laura Medeghini; Silvano Mignardi; Aida Maria Conte; Tilde de Caro (Heritage, 2024)
We report here the results of a multi-analytical approach to characterize twelve Roman coins dating from the third century B.C. to fifth century A.D. that were found in the surroundings of Rome and for which the year of minting is determined by numismatic analysis. The coins were studied using SEM-EDS, EMPA, XRD, and FTIR techniques, enabling semi-quantitative and quantitative determinations of the chemical and mineralogical composition of the alloys and corrosion products. SEM-EDS analyses highlighted the occurrence of corrosion products on the surfaces and wide chemical variations due to selective enrichment or depletions of the alloying metals. The EMP analyses showed that three of the twelve coins are made of copper (1), one is a copper–tin alloy (2), five are copper–tin–lead alloys with elements in different proportions (3), two are copper–lead alloys (4), and another one is a subaerata coin (5). In addition, the physical parameters of the coins, i.e., density, weight, and diameters, were measured to have an overall characterization.